2013
DOI: 10.1590/s0034-76122013000600007
|View full text |Cite
|
Sign up to set email alerts
|

Are public officials really less satisfied than private sector workers?A comparative study in Brazil

Abstract: This research aims to compare the public and private sectors with regard to satisfaction at work. We conducted a survey with 670 professionals from both sectors in Brazil. The results of variance analysis confirm previous researches indicating that public officials are less satisfied with their work than private sector workers. However, this result does not repeat when we evaluate the satisfaction dimensions. For instance, public officials reported being more satisfied than private sector workers with regard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
(44 reference statements)
4
12
0
6
Order By: Relevance
“…However, the wages rates in Egyptian public sector are low and have not satisfied public employees with a noticeable public-private earnings gap. The current results confirm previous research (Borges, 2013) showing that public sectors are less satisfied with their income than private sector workers. In contrast, other study from Philippines reported that public sector workers received higher hourly wages than private sector workers (Molato, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…However, the wages rates in Egyptian public sector are low and have not satisfied public employees with a noticeable public-private earnings gap. The current results confirm previous research (Borges, 2013) showing that public sectors are less satisfied with their income than private sector workers. In contrast, other study from Philippines reported that public sector workers received higher hourly wages than private sector workers (Molato, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Asst. Prof. Dr. Renata Borges conducted a comparative study on job satisfaction among 670 professionals from the public and private sector in Brazil (Borges, 2013). She has found that the overall level of job satisfaction is significantly higher in the public sector than in the private sector.…”
Section: Job Satisfaction and Employees From Private And Public Sectormentioning
confidence: 99%
“…In the study carried out by Borges (2013), it was identified that the worker in the public sector is more satisfied than those in the private sector in terms of stability; however, with regard to growth and compensation this situation is reversed.…”
Section: Job Satisfactionmentioning
confidence: 99%